Loneliness and depression in the institutionalized elderly - Ribeiro, Maria Isabel (2014)
Institutionalized elderly people often experience feelings of depression and loneliness. However, there are strategies to combat these problems allowinga better quality of life. Objectives To know the feelings of the elderly in relation to their life. To determine the degree of depression. To verify if loneliness is associated with depression. Methods A cross-sectional, quantitative, observational and analytical study was developed. A questionnaire was developed containing socio demographic questions, the Geriatric Depression Scale and the UCLA Loneliness Scale. A sample of 62 elders (40 women e 22 menaged between 40 and 99 years) that were institutionalized at the Santa Casa de Misericórdia de Vinhais was collected. SPSS 21.0 was used to compute descriptive statistics and Spearman correlation test. Results It was found that 46.8% of respondents had moderate depression and 45.2% had severe depression. There was no evidence of minor depression among elders. The Spearman correlation test show that there is a significant correlation between the Depression and Loneliness (rho=0,472), this means that the correlation is positive and moderate. Conclusions Institutionalized elderly presented moderate and severe depressionlevels. Depression is, significantly, associated with loneliness.The results highlight the need to adopt new strategies for healthy aging, specifically, strategies to decrease the loneliness of the elderly.